Religion and science fiction - Jenkins, Timothy (Images of elsewhere, 2025)
"'Flying saucers come from outer space - except, as Timothy Jenkins observes in this persuasive and enjoyable volume, they also come from the pages of nineteenth-century occult texts. Jenkins ably traces the connections between Madame Blavatsky's messages from spirit masters to Richard Shaver's pulp fiction classic "I Remember Lemuria".' - Matt Tomlinson, Associate Professor, School of Culture, History and Language, Australian National University Flying saucers display characteristic features, transmitted by an important strand of early science fiction, which express religious concerns entangled with new technologies and scientific discoveries. The extraordinary universe discovered by late nineteenth century advances in the sciences, with its expansion in both space and time, was populated in spiritualist and other thought by intelligent beings attentive to and bound up with the progress of humankind. This book traces the appearance of these interplanetary guardians, active at every level from the atom to the Cosmos, and uses a pulp science fiction story from 1945 to describe how this theosophical worldview was expanded to explain important aspects of contemporary American wartime society, in this fashion preparing the landscape for the coming of the flying saucers"--